Plano experimental para características do rácemo de mamoneira em diferentes espaçamentos entre plantas - Paludo, André Luiz (2009)
The cultivation of castor beans presents considerable advances in recent years, because it is a promising crop for production of biodiesel. The planning of experiments for evaluation the productivity of castor beans is important to qualify the search results. The objectives of this study were to determine the appropriate plot size and number of repetitions and the influence of spacing between plants in the experimental culture of castor oil.The experiment with the hybrid Lyra, with row spacing of 1.2 m, was conducted at the experimental area of the Federal University of Santa Maria in 2007. Were evaluated in each plant: number of racemes, fruit weight, average length of racemes and number of fruit, with identification of the plant by the number of rows and number of plants within the row. The optimum plot size is eight plants for all spacings and for all variables. However, the area of optimum plot size in each space depends on the area occupied by the basic unit. Thus the area of the plot is: 3.84 m2, 5.76 m2 and 7.68 m2 for the spacing between plants of 0.4 m, 0.6 m 0.8 m, respectively. The size of plot and/or the experimental area depends on the number of plants.